A balance of life and livelihoods - Williams, Davd (Technical Centre for Agricultural and Rural Cooperation, 2009)
Faced with difficult choices, a Maasai community in Tanzania was able to get an accurate picture of their land resources with the help of conservationists and GPS receivers